Gene Transmission in the One Health Microbiosphere and the Channels of Antimicrobial Resistance - Baquero, Fernando; Coque, Teresa M.; Martínez, José-Luis; Aracil-Gisbert, Sonia; Lanza, Val F. (Frontiers in Microbiology, 2019)
Antibiotic resistance is a field in which the concept of One Health can best be illustrated. One Health is based on the definition of communication spaces among diverse environments. Antibiotic resistance is encoded by genes; however, these genes are propagated in mobile genetic elements, circulating among bacterial species and clones that are integrated into the multiple microbiotas of humans, animals, food, sewage, soil, and water environments. The dynamics and evolution of antibiotic resistance depend on the communication networks linking all these ecological, biological, and genetic entities. These communications occur by environmental overlapping and merging, a critical issue in countries with poor sanitation, but also favored by the homogenizing power of globalization. The overwhelming increase in the population of highly uniform food animals has contributed to the parallel increase in the absolute size of their microbiotas, consequently enhancing the possibility of microbiome merging between humans and animals. This process of microbial community coalescence might lead to shared microbiomes in which the spread of antibiotic resistance (of human, animal, or environmental origin) is highly facilitated. Intermicrobiome communication is mainly exerted by shuttle bacterial species (or clones within species) belonging to generalist taxa, able to multiply in the microbiomes of various hosts, including humans, animals, and plants. Their integration into local genetic exchange communities fosters antibiotic resistance gene flow, following the channels of accessory genome exchange among bacterial species. These channels delineate a topology of gene circulation, including dense clusters of species with frequent historical and recent exchanges. The ecological compatibility of these species, sharing the same niches and environments, determines the possibilities of exchange. In summary, the fertility of the One Health approach to antibiotic resistance depends on the progress of understanding multihierarchical (multilevel) systems, encompassing communications among environments (macro/microaggregates), communications among microbiotas (communities), communications among bacterial species (clones), and communications among mobile genetic elements.